An associative analysis of object memory - Robinson, Jasper; Bonardi, Charlotte (Elsevier, 2014)
Different aspects of recognition memory in rodents are commonly assessed using variants of the spontaneous object recognition procedure in which animals explore objects that differ in terms of their novelty, recency, or where they have previously been presented. The present article describes three standard variants of this procedure, and outlines a theory of associative learning, SOP [1] which can offer an explanation of performance on all three types of task. The implications of this for theoretical interpretations of recognition memory and the procedures used to explore it are discussed.